Cone-Beam Computed Tomography Accuracy for Morphological and Morphometric Evaluation of Mandibular Condyles Using Small FOV and Small Voxel Size - Arifin, Sariyani Pancasari Audry; Kiswanjaya, Bramma; Priaminiarti, Menik; Iskandar, Hanna H. Bachtiar (Journal of Indonesian Dental Association, 2023)
The objective of this study is to evaluate the accuracy of cone beam computed tomography (CBCT) in determining and visualizing the morphology and morphometry of the mandibular condyle. Narrative reviews with article searches were carried out through NCBI's PubMed database and Scopus from September 2021–October 2021, with the inclusion criteria articles published in 2011–2021. The temporomandibular joint (TMJ) has a crucial role and is closely related to the masticatory system. The diagnosis of temporomandibular disorder (TMD) is not easy and is complex enough to require a comprehensive clinical and radiographic examination. Pathological changes such as erosion of the condyle, fracture, ankylosis, dislocation, and osteophyte can be well seen using CBCT imaging. CBCT images obtained with smaller field of view (FOV) have smaller a voxel size and a higher image resolution. FOV or scan volume refers to the anatomical area that will be included in the data volume or the area of the patient that will be irradiated. The dimension of FOV depends on the detector size and shape, the beam projection geometry, and the ability to collimate the beam. Voxel size is an important component of image quality, related to both the pixel size and the image matrix. Selection of small FOV and small voxel size is recommended because they provide better visualization and detail for the evaluation of morphology and morphometry of the condyle, especially the detection of erosion and defects on the condyle surface.